Institusionalisasi Partai Politik: Studi Terhadap Masa Jabatan Pimpinan Parpol di Indonesia 2019-2023 - Muhammad Haqiqi; Rizki Maulana Syafei; Audina El Rahma (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
The term of office of political party leaders is still being debated both in Article 23 paragraph (1) of Law Number 2/2011 concerning Political Parties, as well as in the test at the Constitutional Court with Decision Number 69 / PUU-XXI / 2023. The location of the debate is because the Political Party Law orders the regulation to the internal regulations of political parties, which is felt to be undemocratized in the level of regeneration of political party leaders. This research is present to compare the tenure of political party leaders in parliament and then determine the most ideal tenure of political party leaders from these parties based on the concept of institutionalization of political parties. This research method is juridical - normative through conceptual approach and statutory approach to legal materials related to the theme. This research concludes, from the internal regulations of the parties, the requirements for party leaders to the mechanism for electing political party leaders in general have the same style. Specifically related to the term of office of political parties, only the United Development Party (PPP) and the Prosperous Justice Party (PKS) have a period of time regulated in the party's internal regulations. Based on the concept of institutionalization of political parties from the comparative study, the ones that are close to the ideal concept are the Prosperous Justice Party (PKS) and the United Development Party (PPP).